Hemorrhagic disease of the newborn : methodical recommendations students of the 5 year of the medical faculty - Krutenko, Natalia V.; Voloshyn, Kostiantin V.; Крутенко, Наталія Володимирівна; Волошин, Костянтин Вікторович (Kharkiv : V. N. Karazin Kharkiv National University, 2020)
Methodоdical recommendations contain information concerning of the etiology, pathogenesis, classification, diagnosis and treatment of hemorrhagic disease of the newborn. Features of vitamin K exchange, hemostasis system in newborns are described in details. Recommendations for prevention of bleeding in children in the neonatal period are given. The methodical recommendations were developed on the basis of the Program of the discipline "Pediatrics, Children's Infectious Diseases" for students of higher medical educational institutions of III-IV levels of accreditation, approved by the Ministry of Health of Ukraine. These methodical recommendations are intended for students of the 5th year of English-speaking medical faculties.

Методичні рекомендації містять інформацію щодо етіології, патогенезу, класифікації, діагностики та лікування геморагічної хвороби новонародженого. Детально описано особливості обміну вітаміну К, системи гемостазу у новонароджених. Надано рекомендації щодо профілактики кровотеч у дітей в неонатальному періоді. Методичні рекомендації розроблено на основі програми дисципліни «Педіатрія, дитячі інфекційні хвороби» для студентів вищих медичних навчальних закладів III–IV рівнів акредитації, затвердженої МОЗ України. Ці методичні рекомендації призначено для студентів 5-го курсу медичного факультету англомовного навчання.
Геморагічна хвороба новонародженого : методичні рекомендації для студентів 5 курсу медичного факультету
Навчальне видання
Keywords: MEDICINE; SOCIAL SCIENCES; hemorrhagic disease; newborn; соagulation; vitamin K; thrombocytopenia; геморагічна хвороба; новонароджений; коагуляція; вітамін К; тромбоцитопенія